Development Of Student Volleyball In Uzbekistan (Pedagogical Cluster-Journal of Pedagogical Developments, 2024)
the article discusses the issue of popularization and development of student volleyball in Uzbekistan. It serves as a means of physical development and health promotion for the general population, and, as a result, is very popular among students around the world.